2012
DOI: 10.1155/2012/651805
|View full text |Cite
|
Sign up to set email alerts
|

Reticulon Protein-1C: A New Hope in the Treatment of Different Neuronal Diseases

Abstract: Reticulons (RTNs) are a group of membrane proteins localized on the ER and known to regulate ER structure and functions. Several studies have suggested that RTNs are involved in different important cellular functions such as changes in calcium homeostasis, ER-stress-mediated cell death, and autophagy. RTNs have been demonstrated to exert a cancer specific proapoptotic function via the interaction or the modulation of specific proteins. Reticulons have also been implicated in different signaling pathways which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Previous studies suggested that RTN1 might be involved in the pathogenesis of human diseases, principally neurodegenerative disorders. 21 , 23 , 26 To determine whether RTN1 is involved in cerebral ischemia/reperfusion (I/R) injury, we performed western blot to detect the expressions of the three splice variants of RTN1 in the brain tissue samples of MCAO rats. Among the three splice variants of RTN1, only RTN1-C staining was significantly upregulated by ischemia/reperfusion in rat brains ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that RTN1 might be involved in the pathogenesis of human diseases, principally neurodegenerative disorders. 21 , 23 , 26 To determine whether RTN1 is involved in cerebral ischemia/reperfusion (I/R) injury, we performed western blot to detect the expressions of the three splice variants of RTN1 in the brain tissue samples of MCAO rats. Among the three splice variants of RTN1, only RTN1-C staining was significantly upregulated by ischemia/reperfusion in rat brains ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“… 20 Notably, the reticulon family gene 1 (RTN1) was characterized by antibodies that stained a subset of neuroendocrine tissues and was formerly called neuroendocrine specific protein. 21 The RTN1 family has three variants, namely, RTN1-A, RTN1-B and RTN1-C. 22 It has been reported that RTN1-A is a novel mediator of chronic kidney disease progression that promotes renal injury through ER stress. 23 In addition, human RTN1-A and RTN1-B, but not RTN1-C, were found to bind with AP50, a component of the AP-2 adaptor complex that mediates endocytosis.…”
mentioning
confidence: 99%
“…ER, has been implicated in the pathogenesis of various diseases by interfering with calcium homeostasis and autophagy, resulting in ER stress mediated cell death(Di Sano & Piacentini, 2012; …”
mentioning
confidence: 99%
“…In contrast to the highly conserved C-terminal RHD, the N-terminal regions of RTNs display no sequence similarity at all, even among paralogs within the same species [16]. There is growing evidence showing that RTNs are a group of membrane proteins localized in ER and known to regulate the structure and function of ER [12]. Furthermore, the expression patterns of RTNs and their splice isoforms can be variable, even within the same organism [10,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence is particularly pertinent for the RTN1-C [11][12][13]. RTN1-C protein is a membrane protein localized in the ER and expressed in the nervous system, and its function is far from clear [14].…”
Section: Introductionmentioning
confidence: 99%